Nigella sativa seeds protect against hepatotoxicity and dyslipidemia induced by carbon tetrachloride in mice - Amina E. Essawy , , Ashraf M. Abdel-Moneim , , Latifa I. Khayyat, Aglal A. Elzergy (Journal of Applied Pharmaceutical Science)
The present study was conducted to evaluate the hepatoprotective effects of aqueous seed extract of Nigella sativa (black seed) on carbon tetrachloride (CCl4) induced liver damage in Swiss albino mice. CCl4 (1.9 ml/kg b.w.) was given orally every other day for three weeks. Aqueous suspension of N. sativa seeds (50 mg/kg b.w.) was given orally every other day alternated with CCl4 for three weeks. Blood was collected for the assessment of serum marker enzymes ( ALT, AST ,ALP and LDH) and lipid profile (triglycerides, total cholesterol, HDL and total lipids), while liver tissue was used for histopathological assessment. Serum levels of liver enzymes and lipid contents were significantly increased in animals treated with CCL4 as compared to control. Histopathological observations, also revealed severe damage in the structure of liver tissue in animals intoxicated with CCL4. Combined treatment of CCL4-exposed animals with N. sativa showed marked improvement in both biochemical and histopathological findings. Only LDH did not affect by N. sativa administration.
Keywords: CCl4,N. sativa,liver enzymes,lipid profile and histopathology.